The Effect of Group Guidance Services with Role Playing Techniques to Improve Emotional Management Skills in Al-Washliyah 12 Perbaungan High School Students - Septi Aulia Lubis; Saiful Akhyar Lubis (Universitas Muhammadiyah Enrekang, 2024)
This study aims to determine the Effect of Group Guidance Services with Role Playing Techniques to Improve the Ability to Manage Emotions in Al-Washliyah 12 Perbaungan High School Students. The model in this study uses a quantitative method, an experimental model of quantitative research can be interpreted as a research method based on the philosophy of positivism, used to research a certain population or sample, data collection using research instruments, data analysis is quantitative/statistical with the aim of testing the hypothesis that has been set. Based on the output of